The Success Phenomenon in Socio-Cultural Management - Kovalenko, Yelena (Socio-Cultural Management Journal, 2021)
Introduction. Significant for modern realities is the strengthening of people’s desire for success, especially in management. However, despite desperate efforts, the vast majority of people do not succeed. This is because people do not understand what success is, its essential basis, and ways to achieve it. At the same time, the cardinal changes that are taking place today under the globalization influence necessitate a new understanding of this phenomenon’s nature. Purpose and methods. The purpose of the article is a theoretical and philosophical analysis of the success phenomenon and identification of causal patterns of its achievement in the socio-cultural management of post-industrial society. The methodological basis of the study is the dialectical principle of cognition, systemic, metaphysical, culturological, psychological, organizational approaches to the study of behavioral processes in management. Results. The existing methodological approaches to the study of the phenomenon of success in the life of an individual and society as a whole are considered. The essence of success as a socio-cultural motivator of human activity and the driving force of management is revealed. Existential types of success and mechanisms of its achievement are defined. The most important personal qualities of the individual are revealed, which guarantee success in the role of a manager. The modern paradigm of management pedagogy is substantiated, with orientation on successful managers’ preparation. Conclusions. The scientific novelty of the research results is to deepen the understanding of the nature of the success phenomenon and the peculiarities of its achievement in the conditions of complicated social relations, uncertainty, and turbulence. The significance of the study is manifested in the addition of management science to new ideas about success as a driving force in management, as well as in the possibility of using these ideas in the process of training business organizations managers.